Streptomyces spp. From the Marine Sponge Antho dichotoma: Analyses of Secondary Metabolite Biosynthesis Gene Clusters and Some of Their Products - Guerrero-Garzón, Jaime Felipe; Zehl, Martin; Schneider, Olha; Rückert, Christian; Busche, Tobias; Kalinowski, Jörn; Bredholt, Harald; Zotchev, Sergey B. (Frontiers in Microbiology, 2020)
Actinomycete bacteria from marine environments represent a potential source for new antibiotics and anti-tumor drugs. Ten strains belonging to the genus Streptomyces isolated from the marine sponge Antho dichotoma collected at the bottom of the Trondheim fjord (Norway) were screened for antibiotic activity. Since only few isolates proved to be bioactive in the conditions tested, we decided to gain an insight into their biosynthetic potential using genome sequencing and analysis. Draft genomes were analyzed for the presence of secondary metabolite biosynthesis gene clusters (BGCs) using antiSMASH software. BGCs specifying both known and potentially novel secondary metabolites were identified, suggesting that these isolates might be sources for new bioactive compounds. The results of this analysis also implied horizontal transfer of several gene clusters between the studied isolates, which was especially evident for the lantibiotic- and thiopeptide-encoding BGCs. The latter implies the significance of particular secondary metabolites for the adaptation of Streptomyces to the spatially enclosed marine environments such as marine sponges. Two bioactive isolates, one showing activity against both yeast and Bacillus subtilis, and one only against yeast were analyzed in details, leading to the identification of cycloheximide, linearmycins and echinomycins that are presumably responsible for the observed bioactivities.